(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human capital is the pivotal of organizational effectiveness and the most valuable asset available to an organization is its people. Retaining employees in their jobs is crucial for any organizational productivity and competitiveness. The shortage of academic staff and inability for higher Education Institutions to attract and retain highly qualified talent is a critical phenomenon in tertiary education. Satisfaction of academic staff will increase productivity and increase research outputs for the universities. The aim of the study was to investigate the impact of compensation, benefits on job satisfaction among academic staff in higher education institutions in a Indian context. There is paucity on research investigating specifically the relationship between compensation, benefits and job satisfaction within the higher education institutions nationally.